1986
DOI: 10.1093/schbul/12.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Vulnerability Indicators, Thought Disorder, and Negative Symptoms

Abstract: Deficits on two continuous performance test versions and the forced-choice span of apprehension task, which are potential vulnerability factors for schizophrenic disorders, were examined in relationship to particular symptoms of schizophrenic disorders, with emphasis on hypothesized relationships to formal thought disorder and negative symptoms. These interrelationships were determined concurrently within a group of 40 schizophrenic patients at an inpatient point. In addition, 32 of these patients were reteste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
183
4
4

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(205 citation statements)
references
References 72 publications
14
183
4
4
Order By: Relevance
“…(3-7 CPT) (Nuechterlein et al, 1986). This refinement of the original A-X CPT (Rosvold et al, 1956) measures focused, sustained attention under immediate memory load conditions.…”
Section: Memory Load Continuous Performance Testmentioning
confidence: 99%
See 2 more Smart Citations
“…(3-7 CPT) (Nuechterlein et al, 1986). This refinement of the original A-X CPT (Rosvold et al, 1956) measures focused, sustained attention under immediate memory load conditions.…”
Section: Memory Load Continuous Performance Testmentioning
confidence: 99%
“…This pattern of findings suggests that formal thought disorder reflects, in part, state-like exacerbations in illness but also might be associated with more stable underlying neurocognitive impairments. This conclusion is supported by longitudinal studies that have found the relationship between thought disorder and discrete neurocognitive deficits to be stronger during periods of stabilization than during acute episodes (Asarnow and MacCrimmon, 1982;Nuechterlein et al, 1986;Pandurangi et al, 1994). Neuropsychologists and experimental psychopathologists have frequently assessed the quality of thinking using proverb interpretation tasks (Lezak, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blurring (degradation) of stimuli enhances the role of early perceptual encoding in performance. Details of stimulus characteristics and projector equipment were given in Nuechterlein et al (1986). The signal/noise discrimination index, d 0 , from signal detection theory was the dependent variable.…”
Section: Neurocognitive Assessmentmentioning
confidence: 99%
“…The partial-report, forced-choice format limits the role of short-term memory and enhances the role of early encoding and search processes. Stimulus characteristics and projector equipment for this version were described in Nuechterlein et al (1986). The accuracy of target detection in 10-letter arrays was the dependent variable.…”
Section: Neurocognitive Assessmentmentioning
confidence: 99%